Emission-line metallicities from the Faint Infrared Grism Survey and VLT/MUSE - Pharo, John; Pasquali, Anna (The astrophysical journal, 2019)
We derive direct-measurement gas-phase metallicities of for 14 low-mass emission-line galaxies at 0.3 < z < 0.8 identified in the Faint Infrared Grism Survey. We use deep slitless G102 grism spectroscopy of the Hubble Ultra Deep Field, dispersing light from all objects in the field at wavelengths between 0.85 and 1.15 μm. We run an automatic search routine on these spectra to robustly identify 71 emission-line sources, using archival data from Very Large Telescope (VLT)/Multi-Unit Spectroscopic Explorer (MUSE) to measure additional lines and confirm redshifts. We identify 14 objects with 0.3 < z < 0.8 with measurable [O iii]λ4363 Å emission lines in matching VLT/MUSE spectra. For these galaxies, we derive direct electron-temperature gas-phase metallicities with a range of . With matching stellar masses in the range of 107.9 M ⊙ < M ⋆ < 1010.4 M ⊙, we construct a mass-metallicity (MZ) relation and find that the relation is offset to lower metallicities compared to metallicities derived from alternative methods (e.g., R 23, O3N2, N2O2) and continuum selected samples. Using star formation rates derived from the Hα emission line, we calculate our galaxies’ position on the Fundamental Metallicity Relation, where we also find an offset toward lower metallicities. This demonstrates that this emission-line-selected sample probes objects of low stellar masses but even lower metallicities than many comparable surveys. We detect a trend suggesting galaxies with higher Specific Star Formation (SSFR) are more likely to have lower metallicity. This could be due to cold accretion of metal-poor gas that drives star formation, or could be because outflows of metal-rich stellar winds and SNe ejecta are more common in galaxies with higher SSFR.
Gesehen am 27.06.2019